ANALISIS EFEKTIVITAS METODE TEBAK GAMBAR DALAM MENGEMBANGKAN BAHASA RESEPTIF SISWA - Khofifah, Eva Nur; Fatimah, Nurul; Tartila, Zakiyana; Ilyas, Muhammad (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2025)
This study aims to examine the effectiveness of using the "guess the picture" media in developing receptive language skills among first-grade students at MI Nurul Huda. This research employs a qualitative approach with a case study design. Data were collected through observations and interviews with teachers and analyzed using thematic analysis techniques. The findings reveal that the use of the "guess the picture" media has a significantly positive impact on the development of students’ receptive language skills at the elementary school/madrasah ibtidaiyah level. Students became more active, enthusiastic, and responsive during the learning process. The "guess the picture" media also contributed to enhancing students' cognitive abilities, such as recognizing new vocabulary related to environmental themes, narrating simple picture stories, and understanding storylines based on a sequence of images. Additionally, careful planning prior to the use of the "guess the picture" media was found to be crucial in supporting successful learning outcomes. Despite encountering some challenges, such as teachers struggling to design engaging media suited to students’ developmental levels, overall, the "guess the picture" media proved to be an effective and efficient tool in developing receptive language skills. This study recommends the use of "guess the picture" media as an innovative and enjoyable learning method to enhance receptive language intelligence in elementary school/madrasah ibtidaiyah students.